2019
DOI: 10.1111/1365-2664.13455
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the fundamental thermal niche of crop pests and diseases in a changing world: A case study on citrus greening

Abstract: 1. Predicting where crop pests and diseases can occur, both now and in the future under different climate change scenarios, is a major challenge for crop management. One solution is to estimate the fundamental thermal niche of the pest/disease to indicate where establishment is possible. Here, we develop methods for estimating and displaying the fundamental thermal niche of pests and pathogens and apply these methods to Huanglongbing (HLB), a vector-borne disease that is currently threatening the citrus indust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 44 publications
1
34
0
1
Order By: Relevance
“…For example, a study on three mosquito-borne diseases, Zika, dengue, and chickungunya transmitted by Aedes aegypti and Aedes albopictus showed that the transmission is likely to occur between 18-34 • C with peak transmission between 26-29 • C [44]. Moreover, the temperatures suitable for the transmission of the plant-borne disease, citrus greening, between 16 • C and 33 • C with peak transmission at 25 • C [45]. Together with our findings, this shows that there are similarities between ectotherm vectors in the way they respond to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on three mosquito-borne diseases, Zika, dengue, and chickungunya transmitted by Aedes aegypti and Aedes albopictus showed that the transmission is likely to occur between 18-34 • C with peak transmission between 26-29 • C [44]. Moreover, the temperatures suitable for the transmission of the plant-borne disease, citrus greening, between 16 • C and 33 • C with peak transmission at 25 • C [45]. Together with our findings, this shows that there are similarities between ectotherm vectors in the way they respond to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the many practical applications related to food production, genome editing can and will be used to solve agricultural issues that directly affect food security, such a citrus greening disease (Taylor et al, 2019), and the high yield losses in C3 plants, such as rice and barely, due to inefficient photorespiration in these crops. A recent report described the construction of three synthetic glycolate metabolic pathways in tobacco chloroplasts with the aim of improving the plant's photosynthetic efficiency.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…These modeling frameworks must therefore be revised and amended if they are to work in epidemiology (40). Ecological niche modeling estimates ecological niches of species by linking spatial occurrence records with environmental covariates, via correlative or mechanistic approaches (41,42). Theory and analytical approaches of ecological niches have been described during the last century (43), especially for biodiversity and conservation studies.…”
Section: Ecological Niche Modeling and Spatial Epidemiologymentioning
confidence: 99%